Henoch-Scholein Purpura (HSP): A Clinico-etiological Study - SN Kareem; N Riyaz (Nepal Journal of Dermatology, Venereology & Leprology)
Background: Henoch–Schönlein (HSP) is a small vessel vasculitis affecting skin and internal organs.